Traumatic arteriovenous fistula. Apropos of a case - Manuel Otero Reyes; Denis González Escalona; Oscar Duménigo Arias; María Victoria Gordis Aguilera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
The traumatisms that affect the extremities represent 80% of all the vascular traumatisms approximately. The inadequate handling of these it contributes to fateful consequences as the loss of the life or of the function of the extremity. The vascular lesions for firearm constitute one of the main causes with the appearance of arteriovenous fistula. We present the case of a 36 year old masculine patient with antecedents of having hurt 1 year ago by firearm in the root of the left thigh goes to present increase of volume of the extremity and difficulty to the march with sensation of fatigue and gravity. To the physical exam increase of volume of the limb more marked affection was verified in the root of the thigh, in the area related with the bullet impact thrill is felt and blow holosistólico is auscultated. The echo doppler and the tomography with contrast use evidenced the presence of a arteriovenous fistula. With this diagnosis was carried out surgical exploration and repair by means of veins bond for exclusion and interference of ilio-femoral arterial implant of politetrafluoroethylene (PTFE). The postoperative evolution was satisfactory with regression of all the clinical signs.